Broad-band EDFA gain flattening by using an embedded long-period fiber grating filter - Dong, X. Y. (2009)
An erbium-doped fiber amplifier (EDFA) gain flattening technique using an embedded long period grating (ELPG) is proposed. By bending the ELPG, due to different coupling strengths yielded from different bending curvatures, it can be used for both the static and dynamic gain flattening despite of the different pump currents of the EDFA. The experimental results demonstrate that the flattened gain region of 34 nm can be achieved within 1 dB ripple.